TAFSIR AL-QUR’AN TENTANG PEREMPUAN (Studi Perbandingan antara Interpretasi Klasik dan Kontemporer): QUR’ANIC EXEGESIS ON WOMEN (A Comparative Study between Classical and Contemporary Interpretations) - Darmawan; Amanuroh, Azizah; Rumsari (Islamic Texts: Journal of Tafsir and Hadith Studies, 2025)
Prophet Joseph is described as a man of steadfastness, especially when he was able to resist and guard himself from the temptations of Al-Aziz's wife, who had fallen in love with him. This story is even immortalized in the Qur'an, Surah Yusuf, verses 23-24. On the other hand, in today's era, adultery and infidelity are rampant, which often occur because there are no boundaries between men and women in social circles. Without being fortified by strong faith, we will all continue to be slaves to our terrible desires. It is from these issues that the author conducted research on exemplary attitudes in the story of Yusuf as. By studying the Qur'an, Surah Yusuf, verses 23-24. How did Yusuf as. behave when faced with such a heavy temptation? What examples should be taken from the story of Yusuf as. as recorded in Surah Yusuf, verses 23-24, for life today? The results of the study show that Yusuf as. demonstrated a high level of integrity when faced with a great trial in the form of the seductive advances of al-'Aziz's wife. Yusuf as.'s integrity encompassed a strong commitment to protecting the trust and maintaining honor, the courage to uphold the truth in the midst of falsehood before him, and self-control. Therefore, it is only fitting that we practice this attitude in the midst of 21st-century life, so that lust no longer reigns supreme within us.